VEGETATION STRUCTURE AND COMPOSITION OF ROAD VERGE AND MEADOW SITES COLONIZED BY CABRERA VOLE (MICROTUS CABRERAE THOMAS) - Santos, Sara M. (2009)
This paper analyses the floristic composition and vegetation structure in road verge and meadow sites colonized by Cabrera vole (Microtus cabrerae Thomas, 1906), a threatened rodent with fragmented distribution in the Iberian Peninsula. Vegetation was sampled in 26 colonized patches in five geographical areas of Southern Portugal. The cover of the herbaceous layer was sampled in 1 × 1 m plots. Several variables related to plant diversity, Raunkiaer lifeforms, taxonomic groups, disturbance and soil properties were assessed. Floristic composition of the herbaceous communities of road verge and meadow sites was different. Indicator species of road verges corresponded mainly to annual grasses and forbs, ruderal and nitrophilous species, along with a few perennials. In meadows, perennial grasses and moisture indicative species were more common. Results suggest that road verges are lower quality habitats for Cabrera vole maintenance, due to high disturbance, low moisture availability during summer and reduced patch surface. Nevertheless, they might provide benefits such as extra foraging and refuge, especially in disturbed areas. Potential ecological effects of road verge management are discussed in the light of species conservation goals.